Negative electrode film-forming additive as well as preparation method and application thereof

By using alkyl boric acid alkoxysilane as an anode film forming additive in lithium-ion batteries, the electrochemical performance decay caused by volume changes and poor circulation performance caused by reaction with electrolyte is solved, and the problem of silicon-based anode material is achieved. More stable cycle performance and higher safety.

CN119447458APending Publication Date: 2025-02-14SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411619962.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, silicon-based anode materials tend to deteriorate electrochemical performance due to volume changes during the deintercalation process of lithium ions, and easily react with the electrolyte to lead to poor circulation performance.

Method used

An alkyl boric acid alkoxysilane is used as the negative electrode film forming additive. Through its unique chemical properties and B-O-B crosslinking network structure, the volume changes of the silicon-carbon negative electrode are suppressed and the overgrowth of the solid electrolyte interface layer is reduced.

Benefits of technology

It significantly improves the cycle stability and charge and discharge efficiency of the battery, enhances the safety of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005133183190000011
    Figure BDA0005133183190000011
  • Figure BDA0005133183190000021
    Figure BDA0005133183190000021
  • Figure BDA0005133183190000022
    Figure BDA0005133183190000022
Patent Text Reader

Abstract

The invention provides a negative electrode film-forming additive as well as a preparation method and application thereof. The negative electrode film-forming additive is alkyl boric acid alkoxy silane with a specific structure. The passivation film with a compact structure and a stable structure can be preferentially generated on the silicon negative electrode, and oxygen atoms in the structure react with active points of the silicon negative electrode to reduce the activity of the silicon negative electrode, so that the effect of inhibiting the electrolyte from being decomposed on the active points of the silicon negative electrode in the circulation process is achieved; the passivation film with a B-O-B cross-linked network structure has higher flexibility and stability due to the high bond energy characteristic of Si-O bonds, the solid electrolyte film has better ionic conductivity and higher flexibility and stability, continuous consumption of electrolyte caused by silicon particle expansion in the circulation process can be inhibited, interface impedance is reduced, and the service life of the solid electrolyte film is prolonged. And thus, the cycling stability of the silicon-carbon negative electrode system lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode film-forming additive, a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries, as a chemical energy source with high operating voltage, excellent specific energy density, long cycle life and environmental friendliness, have become an indispensable key component in the fields of electronic digital, electric vehicles, energy storage applications and aerospace. Among them, the electrolyte, known as the "liquid of life" of lithium-ion batteries, plays a vital role in the performance of batteries. It mainly includes three components: lithium salt, solvent and additives, which directly affect the cycle stability, charge and discharge rate and safety performance of the battery.

[0003] With the continuous evolution of lithium-ion battery technology, the application prospects of high-energy-density batteries are becoming increasingly broad, especially the silicon-carbon material system. Silicon-carbon negative electrode materials are regarded as the key to improving battery energy density due to their extremely high theoretical specific capacity. However, this material system also faces significant challenges: during the lithium ion insertion and extraction process, silicon particles will experience significant expansion and contraction of volume. This physical change will not only cause the particles to break or even pulverize, making them easy to fall off the substrate, but also cause rapid decline in electrochemical performance. In addition, the continuous growth of the solid electrolyte interface layer (SEI) on the surface of silicon particles is due to the continuous side reactions between them and the electrolyte, which further exacerbates the shortcomings of high-energy-density batteries using silicon-carbon negative electrode materials in terms of cycle performance. Summary of the invention

[0004] The main purpose of the present invention is to provide a negative electrode film-forming additive, a preparation method and application thereof, so as to solve the problems in the prior art that silicon-based negative electrode materials are prone to electrochemical performance degradation due to volume changes, and are prone to react with electrolytes resulting in poor cycle performance.

[0005] In order to achieve the above object, according to one aspect of the present invention, a negative electrode film-forming additive is provided. The negative electrode film-forming additive is an alkyl boric acid alkoxysilane having a structure shown in general formula (I):

[0006]

[0007] In the general formula (I), R1, R2 and R3 are independently selected from C1 to C15 straight chain or branched alkyl groups; R4 is selected from C2 to C18 straight chain or branched alkylene groups. The alkyl boric acid alkoxysilane additive of the present application can effectively inhibit the volume change of the silicon-carbon negative electrode and reduce the excessive growth of the SEI layer due to its unique chemical properties and optimized design of the BOB cross-linked network structure, thereby improving the cycle stability and charge and discharge efficiency of the battery and significantly enhancing the safety of the battery.

[0008] Furthermore, in the general formula (I), R1, R2 and R3 are independently selected from C1 to C4 straight chain or branched alkyl groups; and / or, R4 is selected from C2 to C10 straight chain or branched alkylene groups; preferably, R1, R2 and R3 are independently selected from C1 to C4 straight chain alkyl groups; and / or, R4 is selected from C2 to C10 straight chain alkylene groups; more preferably, R1, R2 and R3 are independently selected from methyl, ethyl or propyl groups, and R4 is selected from ethylene, propylene, butylene, pentylene, hexylene, heptylene or octylene.

[0009] Furthermore, the negative electrode film-forming additive includes

[0010] The above-mentioned negative electrode film-forming additives are more conducive to forming a flexible and stable BOB cross-linked network structure on the negative electrode surface, thereby more effectively inhibiting the volume change of the silicon-carbon negative electrode and reducing the excessive growth of the SEI layer, thereby further reducing the capacity decay of the battery during the cycle process and extending the service life of the battery.

[0011] According to another aspect of the present invention, a method for preparing the above-mentioned negative electrode film-forming additive is provided. The preparation raw materials include α-olefin boric acid and alkoxysilane. In the presence of a catalyst, the α-olefin boric acid, alkoxysilane and a first solvent are mixed to obtain the negative electrode film-forming additive. The preparation method of the present application is simple to operate, and the product is high in purity and stable.

[0012] Further, the molar ratio of α-olefin boric acid to alkoxysilane is 1:(6-14); and / or, α-olefin boric acid includes one or more of 3-butenyl boronic acid, vinyl boronic acid, 4-pentenyl boronic acid and 5-hexenyl boronic acid; and / or, alkoxysilane includes one or more of methyltrimethoxysilane, methyltriethoxysilane, trimethoxysilane, triethoxysilane, ethyltripropoxysilane and methyltrimethoxysilane. The above types of raw materials cooperate with each other and have better compatibility.

[0013] Further, the catalyst includes one or more of (Ph3P)2NiCl2, H2PtCl6 and (Ph3P)2PdCl2; and / or, the first solvent includes one or more of ethanol, methanol and acetone; and / or, the mixing further includes the steps of heating reflux and rotary evaporation in sequence, preferably, the heating reflux temperature is 40-100°C, the time is 2-48h; and / or, the rotary evaporation temperature is 30-50°C, the pressure is 0.1-1MPa, and the time is 0.5-1h. Under the above conditions, the reaction is more fully carried out, the yield of the product is higher, and the side reactions are less.

[0014] According to another aspect of the present invention, an electrolyte is provided, comprising the above-mentioned negative electrode film-forming additive, a lithium salt and a second solvent. As mentioned above, the additive of the present application can effectively inhibit the volume change of the silicon-carbon negative electrode and reduce the excessive growth of the SEI layer. The electrolyte comprising the above-mentioned additive has fewer side reactions with the negative electrode material and is not easy to decompose.

[0015] Further, the lithium salt includes one or more of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(pentafluoroethylsulfonylimide), lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorosulfonylimide), lithium difluoro(bis(oxalate)phosphate and lithium tetrafluoro(oxalate)phosphate; and / or, the second solvent includes ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, dicarbonate, or the like. One or more of ethyl ester, ethyl propionate, ethyl methyl carbonate, methyl ether, ethyl ether, succinonitrile, cyclopentane sulfone, methyl formate, ethyl formate, methyl acetate and ethyl acetate; and / or, by weight percentage, the negative electrode film-forming additive accounts for 0.5-9% of the electrolyte, preferably 0.5-2%; and / or, the lithium salt accounts for 7-16% of the electrolyte, preferably 10-15%; and / or, the second solvent accounts for 80-90% of the electrolyte, preferably 85-90%. Under the above conditions, the requirements of energy density, cycle life, safety and cost of the battery can be taken into account.

[0016] According to another aspect of the present invention, a battery is provided, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte comprises the above-mentioned negative electrode film-forming additive. As mentioned above, the electrolyte of the present application has few side reactions with the negative electrode material, is not easy to decompose, and the cycle stability and rate performance of the battery are effectively improved. The battery has a lower risk of thermal runaway under overcharge or high temperature conditions, is safer, and has a longer life.

[0017] Further, the negative electrode has an anode active material, and the anode active material includes one or more of silicon material, silicon-carbon material, silicon oxide-graphite composite material and silicon carbon-silicon oxide composite material; and / or, the positive electrode has a cathode active material, and the cathode active material includes one or more of transition metal phosphate, transition metal oxide lithium salt active material and metal sulfide, preferably NCM523 and / or NCM811; and / or, the diaphragm includes one or more of polyimide, polyethylene, polypropylene and polyethylene terephthalate; preferably, the diaphragm includes one or more of polyethylene and polypropylene. The above-mentioned types of positive and negative electrode materials and diaphragms can cooperate with the electrolyte of the present application to further improve the energy density and cycle stability of the battery.

[0018] The negative electrode film-forming additive alkyl boric acid alkoxysilane of the present invention can preferentially form a dense and stable passivation film on the silicon negative electrode. The oxygen atoms in the structure react with the active points of the silicon negative electrode to reduce its activity, thereby achieving the effect of inhibiting the decomposition of the electrolyte at the active points of the silicon negative electrode during the circulation process; the high bond energy characteristics of the Si-O bond make the passivation film of the BOB cross-linked network structure more flexible and stable. The solid electrolyte membrane has good ionic conductivity, strong flexibility and stability, can inhibit the continuous consumption of electrolyte caused by the expansion of silicon particles during the circulation process, reduce the interface impedance, and thus improve the cycle stability of lithium-ion batteries with silicon-carbon negative electrode systems. DETAILED DESCRIPTION

[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0020] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the numbers used in this way can be interchanged under appropriate circumstances to describe the embodiments of the present invention.

[0021] As described in the background of the present invention, the prior art has the problem that silicon-based negative electrode materials are prone to electrochemical performance degradation due to volume change, and are prone to react with electrolytes, resulting in poor cycle performance. In order to solve the above problems, in a typical embodiment of the present invention, a negative electrode film-forming additive is provided, and the negative electrode film-forming additive is an alkyl boric acid alkoxysilane having a structure shown in general formula (I):

[0022]

[0023] In the general formula (I), R1, R2 and R3 are independently selected from C1 to C15 straight chain or branched chain alkyl groups; R4 is selected from C2 to C18 straight chain or branched chain alkylene groups.

[0024] The negative electrode film-forming additive of the present application, namely alkyl boric acid alkoxysilane, has unique chemical properties and can construct a structurally stable passivation film on the surface of the silicon-based negative electrode, significantly improving the electrochemical performance and cycle stability of the battery. The key is that the electrophilicity and high reduction potential of the boron (B) element make the B-OH bond preferentially form on the surface of the silicon-based negative electrode and develop into a BOB cross-linked network structure. The formation of this structure, on the one hand, can enhance the stability and flexibility of the film, and on the other hand, the oxygen atoms therein react with the active materials in the silicon-based negative electrode, which can effectively reduce the surface activity of the active materials and inhibit the decomposition of the electrolyte during the battery cycle, thereby significantly improving the stability and safety of the battery system.

[0025] In addition, in the negative electrode film-forming additive of the present application, the Si-O bond has a high bond energy, and combined with the flexibility of the chain alkyl (CH2)n, the constructed BOB cross-linked network structure passivation film is not only flexible but also stable, and can effectively inhibit the expansion and contraction of silicon particles during the charging and discharging process, while preventing the active material from falling off the substrate, which is beneficial to improving the electrochemical properties of silicon-based negative electrode materials. In addition, it can also greatly reduce the continuous consumption of electrolyte and reduce the interface impedance.

[0026] In addition, the electrophilicity of the element B in the negative electrode film-forming additive of the present invention allows the element B to react with the F in the electrolyte. - PF6 - Combined with LiF, Li2O, and Li2O2 in SEI, B element can form BF bond and BO bond, which can promote Li + interface transmission and reduce the interface impedance of the battery cell.

[0027] In addition, given the acidic characteristics of the boric acid group, it can neutralize the residual alkali produced on the positive electrode surface during the charging and discharging process, avoiding further decomposition of the electrolyte solvent by the residual alkali under high voltage, stabilizing the positive electrode and inhibiting the production of harmful gases, thereby enhancing the overall safety of the battery.

[0028] In summary, the alkyl boric acid alkoxysilane additive of the present application, due to its unique chemical properties and optimized design of the BOB cross-linked network structure, can effectively inhibit the volume change of the silicon-carbon negative electrode and reduce the excessive growth of the SEI layer, thereby improving the cycle stability and charge and discharge efficiency of the battery, and significantly enhancing the safety of the battery.

[0029] In order to further improve the solubility and reactivity of the negative electrode film-forming additive, the inventors have optimized the length and type of the alkyl group and the alkylene group through a large number of experiments. In a preferred embodiment, in the general formula (I), R1, R2 and R3 are independently selected from straight-chain or branched alkyl groups of C1 to C4; and / or, R4 is selected from straight-chain or branched alkylene groups of C2 to C10; preferably, R1, R2 and R3 are independently selected from straight-chain alkyl groups of C1 to C4; and / or, R4 is selected from straight-chain alkylene groups of C2 to C10; more preferably, R1, R2 and R3 are independently selected from methyl, ethyl or propyl, and R4 is selected from ethylene, propylene, butylene, pentylene, hexylene, heptylene or octylene.

[0030] In a preferred embodiment, the negative electrode film-forming additive comprises

[0031] The above-mentioned negative electrode film-forming additives are more conducive to forming a flexible and stable BOB cross-linked network structure on the negative electrode surface, thereby more effectively inhibiting the volume change of the silicon-carbon negative electrode and reducing the excessive growth of the SEI layer, thereby further reducing the capacity decay of the battery during the cycle process and extending the service life of the battery.

[0032] In another typical embodiment of the present invention, a method for preparing the above-mentioned negative electrode film-forming additive is also provided, wherein the raw materials for preparation include α-olefin boronic acid and alkoxysilane, and the α-olefin boronic acid, alkoxysilane and a first solvent are mixed in the presence of a catalyst to obtain the negative electrode film-forming additive. The preparation method of the present application is simple to operate, and the product is high in purity and stable.

[0033] The inventors optimized the ratio and type of reactants. In a preferred embodiment, the molar ratio of α-olefin boric acid to alkoxysilane is 1:(6-14); and / or, α-olefin boric acid includes one or more of 3-butenyl boronic acid, vinyl boronic acid, 4-pentenyl boronic acid and 5-hexenyl boronic acid; and / or, alkoxysilane includes one or more of methyltrimethoxysilane, methyltriethoxysilane, trimethoxysilane, triethoxysilane, ethyltripropoxysilane and methyltrimethoxysilane. The above types of raw materials cooperate with each other and have better compatibility.

[0034] In a preferred embodiment, the catalyst includes one or more of (Ph3P)2NiCl2, H2PtCl6 and (Ph3P)2PdCl2; and / or, the first solvent includes one or more of ethanol, methanol and acetone; and / or, the mixing further includes the steps of heating reflux and rotary evaporation in sequence, preferably, the heating reflux temperature is 40-100°C, the time is 2-48h; and / or, the rotary evaporation temperature is 30-50°C, the pressure is 0.1-1MPa, and the time is 0.5-1h. Under the above conditions, the reaction is more fully carried out, the yield of the product is higher, and the side reactions are less.

[0035] In another typical embodiment of the present invention, an electrolyte is also provided, comprising the above-mentioned negative electrode film-forming additive, a lithium salt and a second solvent. As mentioned above, the additive of the present application can effectively inhibit the volume change of the silicon-carbon negative electrode and reduce the excessive growth of the SEI layer. The electrolyte comprising the above-mentioned additive has fewer side reactions with the negative electrode material and is not easy to decompose.

[0036] The inventors optimized the types of lithium salt and solvent in the electrolyte. In a preferred embodiment, the lithium salt includes one or more of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium perchlorate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, bis(pentafluoroethylsulfonyl imide) lithium, bis(trifluoromethylsulfonyl imide) lithium, bis(fluorosulfonyl imide) lithium, difluoro(bisoxalate) lithium phosphate and tetrafluoro(oxalate) lithium phosphate, preferably lithium hexafluorophosphate; and / or, the second solvent includes one or more of organic carbonates, ionic liquids, polyethers, aromatic ethers, C1-C40 alkyl ethers, cyclic ethers, carboxylates, sulfones, nitriles, dinitriles and polynitriles, preferably ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl propionate, methyl ethyl carbonate, methyl ether, ethyl ether, succinonitrile, cyclopentane sulfone, methyl formate, ethyl formate, methyl acetate and ethyl acetate, more preferably propylene carbonate, dimethyl carbonate and diethyl carbonate. The negative electrode film-forming additive of the present application has better compatibility with the above-mentioned types of lithium salts and solvents, and the conductivity and stability of the electrolyte are better.

[0037] After a large number of experiments, the inventor optimized the ratio of the electrolyte. In a preferred embodiment, the negative electrode film-forming additive accounts for 0.5-9% of the electrolyte, preferably 0.5-2% by weight; and / or, the lithium salt accounts for 7-16% of the electrolyte, preferably 10-15%; and / or, the second solvent accounts for 80-90% of the electrolyte, preferably 85-90%. If the content of the negative electrode film-forming additive or lithium salt is too much, the viscosity of the electrolyte may be too high, affecting the transmission rate of lithium ions, and may also cause the SEI film to be too thick or uneven, thereby affecting the electrochemical performance and cycle stability of the battery. If the content of the negative electrode film-forming additive is too little, the formation of the SEI film may be incomplete or unstable, thereby increasing the side reaction between the negative electrode material and the electrolyte, generating gas, and then affecting the cycle performance and safety of the battery. If the content of the lithium salt is too little, it may affect the charge and discharge capacity and energy density of the battery, and may also affect the formation of the SEI film, which may easily lead to direct oxidation of the electrode material, thereby affecting the cycle stability and life of the battery. Under the above conditions, the battery's energy density, cycle life, safety and cost requirements can be taken into account.

[0038] In another typical embodiment of the present invention, a method for preparing the above-mentioned electrolyte is also provided, comprising the following steps: mixing a lithium salt and a second solvent, and then adding a negative electrode film-forming additive to obtain an electrolyte. The preparation process of the present application is simple, efficient, and easy to control, and is suitable for the production of electrolytes of different scales. The obtained electrolyte has good quality and high production efficiency.

[0039] In another typical embodiment of the present invention, a battery is provided, including a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte includes the negative electrode film-forming additive. As mentioned above, the electrolyte of the present application has few side reactions with the negative electrode material, is not easy to decompose, and the cycle stability and rate performance of the battery are effectively improved. The battery has a lower risk of thermal runaway under overcharge or high temperature conditions, is safer, and has a longer life.

[0040] In a preferred embodiment, the negative electrode has an anode active material, and the anode active material includes one or more of silicon material, silicon-carbon material, silicon oxide-graphite composite material and silicon carbon-silicon oxide composite material; the positive electrode has a cathode active material, and the cathode active material includes one or more of transition metal phosphate, transition metal oxide lithium salt active material and metal sulfide, preferably NCM523 and / or NCM811; the diaphragm includes one or more of polyimide, polyethylene, polypropylene and polyethylene terephthalate; preferably, the diaphragm includes polyethylene and / or polypropylene. The above-mentioned types of positive and negative electrode materials and diaphragms can cooperate with the electrolyte of the present application to further improve the energy density and cycle stability of the battery.

[0041] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0042] Example 1

[0043] Preparation of negative electrode film-forming additives:

[0044] In the presence of catalyst (Ph3P)2NiCl2, 3-butenylboric acid and methyltrimethoxysilane (the molar ratio of the two is 1:8) are mixed evenly in anhydrous ethanol, and refluxed under closed conditions at 70°C to react for 5 hours. The intermediate product is subjected to reduced pressure rotary evaporation at 40°C and 0.5MPa for 1 hour to remove ethanol and unreacted raw material methyltrimethoxysilane to obtain a negative electrode film-forming additive.

[0045] Specifically, the reaction equation of 3-butenylboronic acid and methyltrimethoxysilane is as follows:

[0046]

[0047] Preparation of electrolyte:

[0048] Calculated by weight percentage, the components of the electrolyte include: 87.5% solvent (propylene carbonate, dimethyl carbonate and diethyl carbonate in a weight ratio of 2:3:5), 12% lithium salt (lithium hexafluorophosphate), and 0.5% negative electrode film-forming additive.

[0049] In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), the solvents were mixed evenly, and lithium salt was slowly added. After the lithium salt was completely dissolved, a negative electrode film-forming additive was added and stirred evenly to obtain an electrolyte.

[0050] Preparation of positive electrode materials:

[0051] A solid substance (in terms of weight percentage, including 91% NCM523 (i.e., the molar ratio of Ni, Co, and Mn is 5:2:3), 4% acetylene black, and 5% binder PVDF) and N-methylpyrrolidone are mixed to form a slurry, which is then coated on a 12-micron thick aluminum foil, dried, and then roll-pressed to obtain a positive electrode sheet.

[0052] Preparation of negative electrode materials:

[0053] The solid material (comprising 86% silicon carbon, 10% acetylene black and 4% styrene-butadiene rubber as a binder, by weight percentage) was mixed with deionized water to form a slurry, which was then coated on an 8-micron thick copper foil, dried and rolled to obtain a negative electrode sheet.

[0054] Preparation of the battery:

[0055] In a dry environment with a leakage point ≤-50℃, stack the positive electrode sheet, diaphragm (polyethylene), and negative electrode sheet in sequence to ensure that the diaphragm completely separates the positive electrode sheets and the negative electrode completely covers the positive electrode. The battery cells are made by stacking the sheets and encapsulated in an aluminum-plastic film of a fixed size using glue-attached pole ears to form a soft-pack battery to be filled with liquid. Subsequently, the electrolyte is injected into the soft-pack battery, sealed, formed, aged, and sealed twice to obtain a battery.

[0056] Example 2

[0057] The only difference from Example 1 is:

[0058] Preparation of negative electrode film-forming additives:

[0059] In the presence of a catalyst (H2PtCl6), vinylboric acid and methyltriethoxysilane (the molar ratio of the two is 1:12) are evenly mixed in anhydrous ethanol, and refluxed at 60°C in a closed condition to react for 10 hours. The intermediate product is subjected to reduced pressure rotary evaporation at 40°C and 0.5MPa for 1 hour to remove ethanol and unreacted raw material methyltriethoxysilane to obtain a negative electrode film-forming additive.

[0060] Specifically, the reaction equation of vinylboric acid and methyltriethoxysilane is as follows:

[0061]

[0062] Preparation of electrolyte:

[0063] Calculated by weight percentage, the components of the electrolyte include: 87% solvent (propylene carbonate, dimethyl carbonate and diethyl carbonate in a weight ratio of 2:3:5), 12% lithium salt (lithium hexafluorophosphate), and 1% negative electrode film-forming additive.

[0064] Example 3

[0065] The only difference from Example 1 is:

[0066] Preparation of negative electrode film-forming additives:

[0067] In the presence of a catalyst (H2PtCl6), vinylboric acid and trimethoxysilane (the molar ratio of the two is 1:9) are evenly mixed in anhydrous ethanol, and refluxed under closed conditions at 85°C to react for 12 hours. The intermediate product is subjected to reduced pressure rotary evaporation at 40°C and 0.5MPa for 1 hour to remove ethanol and unreacted raw trimethoxysilane to obtain a negative electrode film-forming additive.

[0068] Specifically, the reaction equation of vinylboric acid and trimethoxysilane is as follows:

[0069]

[0070] Preparation of electrolyte:

[0071] Calculated by weight percentage, the components of the electrolyte include: 86.5% solvent (propylene carbonate, dimethyl carbonate and diethyl carbonate in a weight ratio of 2:3:5), 12% lithium salt (lithium hexafluorophosphate), and 1.5% negative electrode film-forming additive.

[0072] Example 4

[0073] The only difference from Example 1 is:

[0074] Preparation of negative electrode film-forming additives:

[0075] In the presence of a catalyst (H2PtCl6), 4-pentenylboric acid and triethoxysilane (the molar ratio of the two is 1:14) are evenly mixed in anhydrous ethanol, and refluxed under closed conditions at 75°C to react for 18 hours. The intermediate product is subjected to reduced pressure rotary evaporation at 40°C and 0.5MPa for 1 hour to remove ethanol and unreacted raw material triethoxysilane to obtain a negative electrode film-forming additive.

[0076] Specifically, the reaction equation of 4-pentenylboronic acid and triethoxysilane is as follows:

[0077]

[0078] Preparation of electrolyte:

[0079] Calculated by weight percentage, the components of the electrolyte include: 86% solvent (propylene carbonate, dimethyl carbonate and diethyl carbonate in a weight ratio of 2:3:5), 12% lithium salt (lithium hexafluorophosphate), and 2% negative electrode film-forming additive.

[0080] Example 5

[0081] The only difference from Example 1 is:

[0082] Preparation of negative electrode film-forming additives:

[0083] In the presence of a catalyst (H2PtCl6), 4-pentenylboric acid and ethyltripropoxysilane (the molar ratio of the two is 1:11) are evenly mixed in anhydrous ethanol, and refluxed at 90°C in a closed condition to react for 20 hours. The intermediate product is subjected to reduced pressure rotary evaporation at 40°C and 0.5MPa for 1 hour to remove ethanol and unreacted raw material ethyltripropoxysilane to obtain a negative electrode film-forming additive.

[0084] Specifically, the reaction equation of 4-pentenylboronic acid and ethyltripropoxysilane is as follows:

[0085]

[0086] Preparation of electrolyte:

[0087] Calculated by weight percentage, the components of the electrolyte include: 87.2% solvent (propylene carbonate, dimethyl carbonate and diethyl carbonate in a weight ratio of 2:3:5), 12% lithium salt (lithium hexafluorophosphate), and 0.8% negative electrode film-forming additive.

[0088] Example 6

[0089] The only difference from Example 1 is:

[0090] Preparation of negative electrode film-forming additives:

[0091] In the presence of a catalyst (H2PtCl6), 5-hexenylboric acid and methyltrimethoxysilane (the molar ratio of the two is 1:6) are evenly mixed in anhydrous ethanol and refluxed at 95°C in a closed condition to react for 20 hours. The intermediate product is subjected to reduced pressure rotary evaporation at 40°C and 0.5MPa for 1 hour to remove ethanol and unreacted raw material methyltrimethoxysilane to obtain a negative electrode film-forming additive.

[0092] Specifically, the reaction equation of 5-hexenylboronic acid and methyltrimethoxysilane is as follows:

[0093]

[0094] Preparation of electrolyte:

[0095] Calculated by weight percentage, the components of the electrolyte include: 87.1% solvent (propylene carbonate, dimethyl carbonate and diethyl carbonate in a weight ratio of 2:3:5), 12% lithium salt (lithium hexafluorophosphate), and 0.9% negative electrode film-forming additive.

[0096] Example 7

[0097] The only difference from Example 1 is:

[0098] Preparation of negative electrode film-forming additives:

[0099] In the presence of catalyst (Ph3P)2NiCl2, 3-butenylboric acid and methyltrimethoxysilane (the molar ratio of the two is 1:6) are mixed evenly in methanol, and refluxed under closed conditions at 40°C to react for 48 hours. The intermediate product is subjected to reduced pressure rotary evaporation at 30°C and 1 MPa for 1 hour to remove ethanol and unreacted raw material methyltrimethoxysilane to obtain a negative electrode film-forming additive.

[0100] Example 8

[0101] The only difference from Example 1 is:

[0102] Preparation of negative electrode film-forming additives:

[0103] In the presence of catalyst (Ph3P)2PdCl2, 3-butenylboric acid and methyltriethoxysilane (the molar ratio of the two is 1:14) are mixed evenly in acetone, and refluxed under closed conditions at 100°C to react for 2 hours. The intermediate product is subjected to reduced pressure rotary evaporation at 50°C and 0.1MPa for 0.5h to remove ethanol and unreacted raw material methyltrimethoxysilane to obtain a negative electrode film-forming additive.

[0104] Example 9

[0105] The only difference from Example 1 is:

[0106] Preparation of electrolyte:

[0107] Calculated by weight percentage, the components of the electrolyte include: 90% solvent, 9.5% lithium salt (lithium hexafluoroarsenate), and 0.5% negative electrode film-forming additive.

[0108] Example 10

[0109] The only difference from Example 1 is:

[0110] Preparation of electrolyte:

[0111] Calculated by weight percentage, the components of the electrolyte include: 85% solvent, 14% lithium salt (lithium perchlorate), and 1% negative electrode film-forming additive.

[0112] Embodiment 11

[0113] The only difference from Example 1 is:

[0114] Preparation of electrolyte:

[0115] Calculated by weight percentage, the components of the electrolyte include: 84% solvent, 7% lithium salt, and 9% negative electrode film-forming additive.

[0116] Example 12

[0117] The only difference from Example 1 is:

[0118] Preparation of electrolyte:

[0119] Calculated by weight percentage, the components of the electrolyte include: 83.5% solvent, 16% lithium salt, and 0.5% negative electrode film-forming additive.

[0120] Example 13

[0121] The only difference from Example 1 is:

[0122] Preparation of positive electrode materials:

[0123] A solid substance (including 91% NCM811, 4% acetylene black, and 5% binder PVDF by weight) and N-methylpyrrolidone were mixed to prepare a slurry, which was then coated on a 12-micron thick aluminum foil and rolled after drying to obtain a positive electrode sheet.

[0124] Preparation of negative electrode materials:

[0125] A solid substance (comprising 86% silicon oxide-graphite composite material, 10% acetylene black, and 4% binder styrene-butadiene rubber by weight) is mixed with deionized water to prepare a slurry, which is then coated on an 8-micron thick copper foil, dried, and rolled to obtain a negative electrode sheet.

[0126] Preparation of the battery:

[0127] In a dry environment with a leakage point ≤-50℃, stack the positive electrode sheet, diaphragm (polyethylene), and negative electrode sheet in sequence to ensure that the diaphragm completely separates the positive electrode sheets and the negative electrode completely covers the positive electrode. The battery cells are made by stacking the sheets and encapsulated in an aluminum-plastic film of a fixed size using glue-attached pole ears to form a soft-pack battery to be filled with liquid. Subsequently, the electrolyte is injected into the soft-pack battery, sealed, formed, aged, and sealed twice to obtain a battery.

[0128] Embodiment 14

[0129] The only difference from Example 1 is:

[0130] Preparation of positive electrode materials:

[0131] A solid substance (including 91% NCM523, 4% acetylene black, and 5% binder PVDF by weight percentage) and N-methylpyrrolidone were mixed to prepare a slurry, which was then coated on a 12-micron thick aluminum foil, dried, and rolled to obtain a positive electrode sheet.

[0132] Preparation of negative electrode materials:

[0133] A solid substance (comprising 86% silicon-carbon-silicon oxide composite material, 10% acetylene black, and 4% binder styrene-butadiene rubber by weight) is mixed with deionized water to form a slurry, which is then coated on an 8-micron thick copper foil, dried, and rolled to obtain a negative electrode sheet.

[0134] Preparation of the battery:

[0135] In a dry environment with a leakage point ≤-50℃, stack the positive electrode sheet, diaphragm (polyimide), and negative electrode sheet in sequence to ensure that the diaphragm completely separates the positive electrode sheets and the negative electrode completely covers the positive electrode. The battery cells are made by stacking the sheets and encapsulated in an aluminum-plastic film of a fixed size using glue-attached pole ears to form a soft-pack battery to be filled with liquid. Subsequently, the electrolyte is injected into the soft-pack battery, sealed, formed, aged, and sealed for capacity division to obtain a battery.

[0136] Comparative Example 1

[0137] The only difference from Example 1 is:

[0138] Calculated by weight percentage, the components of the electrolyte include: 86% solvent, 12% lithium salt (lithium hexafluorophosphate), 2% negative electrode film-forming additive (VC, vinylene carbonate), and excluding alkyl boric acid alkoxysilane.

[0139] Comparative Example 2

[0140] The only difference from Example 1 is:

[0141] Calculated by weight percentage, the components of the electrolyte include: 87% solvent, 12% lithium salt (lithium hexafluorophosphate), 1% negative electrode film-forming additive (FEC, fluoroethylene carbonate), and excluding alkyl boric acid alkoxysilane.

[0142] Comparative Example 3

[0143] The only difference from Example 1 is:

[0144] A negative electrode film-forming additive (DTD, vinyl sulfate) is used instead of alkyl boric acid alkoxysilane.

[0145] Comparative Example 4

[0146] The only difference from Example 1 is:

[0147] Calculated by weight percentage, the components of the electrolyte include: 88% solvent, 12% lithium salt (lithium hexafluorophosphate), and no negative electrode film-forming additives.

[0148] Comparative Example 5

[0149] The only difference from Example 1 is:

[0150] Preparation of electrolyte:

[0151] Calculated by weight percentage, the components of the electrolyte include: 77% solvent, 12% lithium salt, and 11% negative electrode film-forming additive.

[0152] Comparative Example 6

[0153] The only difference from Example 1 is:

[0154] Preparation of electrolyte:

[0155] Calculated by weight percentage, the components of the electrolyte include: 87.8% solvent, 12% lithium salt (lithium hexafluorophosphate), and 0.2% negative electrode film-forming additive.

[0156] Comparative Example 7

[0157] Chinese patent with application number 201910129380.1.

[0158] The electrical performance test results of the batteries prepared in the above examples and comparative examples are shown in Table 1.

[0159] Test method:

[0160] Electrical performance test: The battery is formed and divided into different capacities using a battery test cabinet, wherein the formation process is 0.03C constant current charging to 3.0V, 0.05C constant current charging to 3.4V, and 0.1C constant current charging to 3.7V; the aging process is 45℃ for 12 hours; the capacity division process is 0.33C constant current and constant voltage charging to 4.25V, the cut-off current is 0.05C, and 0.33C constant current discharge to 2.75V is repeated 3 times. Then the battery is charged and discharged at 1C / 1C constant current and constant voltage at room temperature (25℃) for 1000 cycles, and the voltage range is set to 2.75~4.25V. After the cycle is completed, the impedance of the battery is tested with an internal resistance meter, and the thickness of the battery is tested with a vernier caliper. The internal resistance growth rate is equal to the difference before and after the cycle divided by the internal resistance of the battery before the cycle, and the thickness growth rate is equal to the difference before and after the cycle divided by the thickness of the battery before the cycle.

[0161] Table 1

[0162]

[0163]

[0164] From the above, it can be seen that compared with the comparative example, the alkyl boric acid alkoxysilane additive of the present application, due to its unique chemical properties and the optimized design of the BOB cross-linked network structure, can effectively inhibit the volume change of the silicon-carbon negative electrode and reduce the excessive growth of the SEI layer. Furthermore, in the soft-pack battery cycle test, the first charge and discharge coulomb efficiency and capacity retention rate of the battery are significantly improved, the internal resistance and battery thickness are reduced, and the impedance growth caused by the reaction of the electrolyte with the lithiated silicon negative electrode during the cycle is effectively suppressed. At the same time, the particle breakage and differentiation caused by repeated lithium insertion and extraction of the silicon negative electrode are protected to a certain extent, thereby improving the cycle stability of the battery.

[0165] In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the electrochemical performance of the battery is even better.

[0166] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A negative electrode film-forming additive, characterized in that: The negative electrode film-forming additive is an alkyl boric acid alkoxysilane having a structure shown in general formula (I): In the general formula (I), R1, R2 and R3 are independently selected from C1 to C15 straight or branched alkyl groups; R4 is selected from C2-C18 straight chain or branched chain alkylene.

2. The negative electrode film-forming additive according to claim 1, characterized in that: In the general formula (I), R1, R2 and R3 are independently selected from C1-C4 straight chain or branched chain alkyl groups; and / or, R4 is selected from a C2-C10 straight or branched alkylene group; Preferably, R1, R2 and R3 are independently selected from C1 to C4 straight chain alkyl groups; and / or, R4 is selected from C2 to C10 straight chain alkylene groups; More preferably, R1, R2 and R3 are independently selected from methyl, ethyl or propyl, and R4 is selected from ethylene, propylene, butylene, pentylene, hexylene, heptylene or octylene.

3. The negative electrode film-forming additive according to claim 1 or 2, characterized in that: The negative electrode film-forming additive comprises One or more of .

4. The method for preparing the negative electrode film-forming additive according to any one of claims 1 to 3, characterized in that: The raw materials include α-olefin boric acid and alkoxysilane. The α-olefin boronic acid, the alkoxysilane and the first solvent are mixed in the presence of a catalyst to obtain the negative electrode film-forming additive.

5. The preparation method according to claim 4, characterized in that: The molar ratio of the α-olefin boric acid to the alkoxysilane is 1:(6-14); and / or, The α-olefin boronic acid includes one or more of 3-butenyl boronic acid, vinyl boronic acid, 4-pentenyl boronic acid and 5-hexenyl boronic acid; and / or, The alkoxysilane includes one or more of methyltrimethoxysilane, methyltriethoxysilane, trimethoxysilane, triethoxysilane, ethyltripropoxysilane and methyltrimethoxysilane.

6. The preparation method according to claim 4 or 5, characterized in that: The catalyst comprises one or more of (Ph3P)2NiCl2, H2PtCl6 and (Ph3P)2PdCl2; and / or, The first solvent comprises one or more of ethanol, methanol and acetone; and / or, The mixing further comprises the steps of heating reflux and rotary evaporation performed sequentially. Preferably, the heating reflux temperature is 40-100°C and the time is 2-48h; and / or the rotary evaporation temperature is 30-50°C, the pressure is 0.1-1MPa and the time is 0.5-1h.

7. An electrolyte, characterized in that: The negative electrode film-forming additive according to any one of claims 1 to 3, a lithium salt and a second solvent.

8. The electrolyte according to claim 7, characterized in that The lithium salt includes one or more of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(pentafluoroethylsulfonylimide), lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorosulfonylimide), lithium difluoro(bis(oxalato)phosphate and lithium tetrafluoro(oxalato)phosphate; and / or, The second solvent comprises one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl propionate, ethyl methyl carbonate, methyl ether, ethyl ether, succinonitrile, sulfolane, methyl formate, ethyl formate, methyl acetate and ethyl acetate; and / or, Calculated by weight percentage, The negative electrode film-forming additive accounts for 0.5-9% of the electrolyte, preferably 0.5-2%; and / or, The lithium salt accounts for 7-16% of the electrolyte, preferably 10-15%; and / or, The second solvent accounts for 80-90% of the electrolyte, preferably 85-90%.

9. A battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The electrolyte includes the negative electrode film-forming additive according to any one of claims 1 to 3.

10. The battery according to claim 9, characterized in that The negative electrode has an anode active material, and the anode active material includes one or more of a silicon material, a silicon-carbon material, a silicon oxide-graphite composite material, and a silicon-carbon-silicon oxide composite material; and / or, The positive electrode has a cathode active material, and the cathode active material includes one or more of transition metal phosphates, transition metal oxide lithium salt active materials and metal sulfides, preferably NCM523 and / or NCM811; and / or, The separator includes one or more of polyimide, polyethylene, polypropylene and polyethylene terephthalate; preferably, the separator includes one or more of polyethylene and polypropylene.

Citation Information

Patent Citations

  • Electrolyte and secondary battery

    CN109786809A